Avaliação da qualidade da política pública Rede Paulista de Incubadoras de Empresas de Base Tecnológica - RPITec - Gomes, Aline Okumoto (Universidade Federal de São Carlos, 2021)
Business incubators are important organizations that meet the needs of companies, providing support for their implementation, development and consolidation in the market. One of the public policies to support incubators is the São Paulo Network of Technology-Based Business Incubators (RPITEc), an initiative of the Government of the State of São Paulo, which aims to foster and strengthen innovation and the movement of these incubators in the State. Despite the relevance of these policies, there is a need to deepen studies regarding their importance in supporting incubators. Thus, the objective of this work was to adapt a questionnaire to assess the quality of public policy for application to the RPITec policy. To achieve the proposed objective, a measurement model was selected in the literature, which has as an evaluation basis, the perceived quality of users in relation to a policy, contemplating five quality determinants represented by project quality, relationship quality, quality result, process quality and reliability. After the selection of this model, the five determinants of quality were adapted, aiming to capture in the best possible way the perception that the respondents have about the RPITec policy. Thus, 21 managers from 11 business incubators accredited to the public policy analyzed participated in this study in order to obtain their perception of the quality of the policy. A Likert-type scale with scores from one to seven was presented at the end of each statement so that respondents could indicate the degree of their disagreement or agreement with it. The scores on the Likert scales, attributed by the managers of the incubators, as a result of their perceptions in each item of the questionnaire, constituted the set of data analyzed statistically. Data analysis took place from a descriptive analysis of the medians of the scores obtained from each statement, since the nature and population distribution projected for them suggested the conduction of statistics in a non-parametric perspective. The proportions of negative, neutral and positive perceptions attributed to assertions about the quality of services provided by the RPITec policy were also calculated. The results found point to the opposite direction to what the hypotheses that guided the development of the present study postulate: while they claim to exist, in the understanding of the incubator managers, a positive evaluation of the services provided by the RPITec policy for each of the quality determinants, those showed that this evaluation was neutral and negative for all of them, except for the first determinant, project quality, whose result was positive for the satisfaction of policy quality. A second step was carried out in this dissertation in order to understand the results of the quality assessment and complement the discussions. Thus, a secondary objective was proposed: to submit the results of the quality assessment found to the policy manager RPITec. The interview was the technique for data collection that supported this step, being conducted virtually together with the manager of the analyzed policy. The interview was semi-structured, containing questions aimed at knowing the dynamics of the work carried out with the incubators and raising possible causes of their low evaluation. It was noticed that the basis for the first alignment of the distortions found in the evaluation is in the communication between the parts.
Evaluation of the quality of public policy São Paulo Network of Technology-Based Business Incubators (RPITEc)
Keywords: Políticas públicas; Incubadoras de empresas; Empresas de Base Tecnológica; RPITec; Qualidade de serviço; Estado de São Paulo; Public policy; Business incubators; Technology-based companies; RPITec; Service quality; State of São Paulo; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::PLANEJAMENTO EM CIENCIA E TECNOLOGIA; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::POLITICA E PLANEJAMENTO GOVERNAMENTAIS; ENGENHARIAS